THE EFFECTIVENESS OF USING RECIPROCAL TEACHING TECHNIQUE ON STUDENTS READING COMPREHENSION AT UPT SMPN 1 MARE (Karya Ilmiah Mahasiswa (KIMA), 2022)
This study were to know the use of reciprocal teaching technique improve the student reading comprehension in descriptive text at UPT SMPN 1 Mare and to find out the effectiveness of reciprocal teaching technique in student reading comprehension at second grade of UPT SMPN 1 Mare. This study employed quantitative research. The subject of this study was the student class VIII 5. The researcher used purposive sampling technique to take randomly 1 class of 5 classes which have the same characteristics in terms of age and the average. The result of this study showed that reciprocal teaching is more effective than the explanatory strategy in teaching reading comprehension . It can be proven from mean of post-test score in experimental class which was 79.24 was higher than before given a treatment (79.24 > 59.68). It means that the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. From the research result, it can be concluded that reciprocal teaching is effective in teaching reading of descriptive text. There are five main points in the study of student perceptions in the used of reciprocal teaching technique on students' reading comprehension they are perception Teaching reciprocal technique is more enjoyable than other method, makes it easier for students to understanded reading texts (descriptive text), increase knowledge about reading comprehension (descriptive text), The students can be motivated, and the students easily adapted.